Promoting Group Justice: Fiscal Policies in Post-Conflict Countries. - Stewart, F; Cobham, A; Brown, G (Political Economy Research Institute (University of Massachusetts at Amherst), 2007)
In the aftermath of violent conflict, governments have an opportunity to address fundamental inequalities between internal groups. As taxation and expenditure policies are developed to rebuild a functional domestic economy and infrastructure, policies can be designed to lessen divisions and promote equity.The authors assert that good data about the status quo on inequality in a country is the first step to addressing it through policy. They then discuss some options for formulating a tax code that addresses distributional issues and increases progressivity. Expenditure planning can also be designed to help create equity in income and non-income resources, such as public services, employment, health and education. The role of aid donors is discussed, particularly as a source of successful strategies gleaned from other post-conflict countries.This study is part of a series on Public Finance in Post-Conflict Environments, published jointly by PERI and New York University's Center on International Cooperation.